An inquiry based learning experience using K-W-L in business communicate on presentations: the student perspective / Ena Bhattacharyya and Nurin Uzma Eizzaty Noor Eizamly - Bhattacharyya, Ena; Noor Eizamly, Nurin Uzma Eizzaty (Akademi Pengajian Bahasa, 2021)
The rapid development of knowledge and technology, particularly in terms of scientific knowledge within the various fields of subject, is one of the most important features of the twenty-first century in which we live today. In line with such technological advancement, teaching learning strategies and methods used for teaching students are not discounted (Alsalhi, 2020). The creativity of educators is even more pronounced during the pandemic (Barber, 2020) where all educators have to resort to online teaching. In such online platforms, student engagement poses a challenge for educators to gain student attention and engagement. Educators need to resort various approaches to gain student engagement. The inquiry-based-learning approach using the “K-W-L” strategy or “Know-What-Learnt” chart organizer encourages all students to take ownership and experience learning beyond the classroom context. The Business Communication students used the “KWL” as part of the inquiry-based learning experience to question, research, analyze, sort, and present their answers according to what they know, learn and learnt about a topic. Findings suggest student’s receptivity to the using the organizer as a learning tool. Learning occurs both outside and within the classroom whether online or offline. Learning becomes student-centered, discussing discoveries and experiences, and reflecting on new-found knowledge. Learning is not mere regurgitation of contents but is actively acquired through independent questioning.